O fenômeno da alienação parental: um olhar por meio do conselho tutelar - Stella, Ana Flávia da Silva (Universidade Federal de São Carlos, 2018)
Parental Alienation (AP), present in Law 12.318 / 10, is relatively new in Brazil and requires further analysis as a growing phenomenon. It is defined, judicially, by parental behaviors of restriction and defamatory campaign of the other parental figure for a child and/or adolescent, configuring a psychological violence. It is a demand received and monitored by different Brazilian institutions and child protection services, especially by Guardianship Council, and has psychological and developmental consequences for children and adolescents inserted in the context of marital dispute and conflict in which the PA occurs. The present study was conducted with 10 guardianship counselors from a Guardianship Council in a city in the interior of the state of São Paulo. It aimed to understand how the participantes deal with and identified the phenomenon of PA, and allow them to act in a way that contributes to the protection of the child or adolescent through the exchange of information on the subject. The initial data indicated that the participants considered that PA referred to the use of the child, in the process of custody dispute or even separation / divorce, for their own benefit or to obtain some kind of advantage. After theoretical presentation and discussion about PA, there was a change in most of the answers to the consideration of PA as psychological violence. There was a greater variation in the importance of “brainwashing” as a determinant of PA, giving more importance, when compared with the pre-test, to variables related to the child (support to the alienating parent, use of inappropriate language, rejection) and parental behaviors (obstruction of access, emotional manipulation). Considering the cultural factors, the participants identified religion and socioeconomic level as variables associated with cases of PA. They pointed out difficulties in identifying the cases, as well as in the vignettes presented during the focus group. It was possible to observe, after the focus group, that they started to consider PA as psychological violence that has both men and women as alienators, and that has negative consequences for child development. It should be noted that the Guardianship Counselors showed resistance to participate (both due to the late observation of the relevance of the theme in the performance, as well as the belief in an increase in assignments). Future research in the area is suggested.
The phenomenon of parental alienation: a look through guardianship council
Keywords: Alienação parental; Violência psicológica; Conselho tutelar.; Parental alienation; Psychological violence; Guardianship council; CIENCIAS HUMANAS::PSICOLOGIA::TRATAMENTO E PREVENCAO PSICOLOGICA